Hydrogels in regenerative medicine and other biomedical applications - Jervis, Peter John (2022)
[Excerpt] It is my great pleasure to be part of this Special Issue in the International Journal of Molecular Sciences—“Hydrogels in Regenerative Medicine and Other Biomedical Applications”. Hydrogels are made up of three-dimensional matrices of hydrophilic polymers, which are held together by chemical or physical crosslinks or by supramolecular assemblies of smaller amphiphilic molecules.